Fundamentos del diseño gráfico de videojuegos - Rojas, Camilo Fabian (Universidad de Boyacá, 2020)
This short article shows the partial results that have been obtained within the research in development, which is part of the PhD in design process that has been carried out at the University of Palermo - Argentina. The research is aimed at the search for a theory centered on the design elements that make up videogames, for this reason the fundamentals of graphic design must be reinterpreted, which have been established taking into account the physical and digital visual products in a general way. For this, in the first phase has raised the use of a hermeneutic method that allows from semiotics to reinterpret the meaning of each design element taking into account the characteristics and qualities of video games.